Cytotoxic and antimicrobial activities of ethyl acetate extract of mangrove plant Scyphiphora hydrophyllacea C. F. Gaertn— Associated fungi - Dian Handayani, Neny sandrawati, Rustini Ruslan, Oga Nestianda, Anzharni Fajrina, Trina Ekawati Tallei (Journal of Applied Pharmaceutical Science, 2019)
Association between mangrove plants with fungi has been explored for many biological activities. The purpose of this study was to determine the antimicrobial and cytotoxic activities of endophytic fungi isolated from mangrove plants Scyphiphora hydrophyllacea C. F. Gaertn. The isolation of endophytic fungus from the mangrove has been carried out by the direct planting method on Sabouraud Dextrose Agar medium. Eleven fungal isolates were recovered and purified. The isolates were cultivated on the rice medium for 1 month and extracted using ethyl acetate. Eleven ethyl acetate extracts were screened for cytotoxic activity by Brine Shrimp Lethality Test method and 3-(4,5-dimethylthiazol- 2-yl)-2,5-diphenyltetrazolium bromide assay and for antimicrobial activity toward some human pathogenic microbes. The results showed that five (45.5%) isolates of endophytic fungi had antimicrobial activity against the growth of Staphylococcus aureus, Escherichia coli, and Candida albicans with a diameter from 9.1 to 21 mm. Furthermore, four extracts (36.4%) were cytotoxic (cell viability < 50%) against T47D cells. Isolate ADSH2 which exhibited the highest cytotoxic activity was identified molecularly as Penicillium chrysogenum. The results of this study indicate that the ethyl acetate of endophytic fungi associated with Scyphiphora hydrophyllacea has the potential to be developed as antimicrobial and anticancer compounds.
Keywords: Antimicrobial activity, cytotoxic activity, mangrove, Penicillium chrysogenum, Scyphiphora hydrophyllacea.